Trichogaster pectoralis Ability in Controlling Eichhornia crassipes Population - Marsely, Debi; ', Windarti; ', Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Trichogaster pectoralis is a root grazer fish and it may be used to control the population of aquatic weeds such as Eichhornia crassipes. To understand the ability of the fish in controlling the weed, a laboratory scaled research has been conducted from April-May 2016. There were 5 treatments applied, namely ±25 grams fish (Bm25), ±50 grams fish (Bm50), ±75 grams fish (Bm75) that were reared in 25 liter tank completed with ±150 grams E. crassipes. As controls, ±150 grams weed was reared in tank without any fish (Ke150) and ±50 grams fish (Ki50) was reared in tank without weed. Results shown that T. pectoralis was able to control E. crassipes population. Each treatment speed up the decrement of E. crassipes population, but the best result was shown by Bm75. In this treatment, the population of E. crassipes reduced into 95.33 grams by the 28th day.Keywords: Trichogaster pectoralis, Eichhornia crassipes, root grazer, weed control